2011
DOI: 10.1111/j.1365-2516.2010.02468.x
|View full text |Cite
|
Sign up to set email alerts
|

Alloantibodies to factor VIII in haemophilia

Abstract: Up to one-third of haemophilia A patients develop factor VIII (FVIII) alloantibodies (inhibitors). The Bethesda assay detects inhibitors but is relatively insensitive. Recently, a new fluorescence-based immunoassay (FLI) was developed for antibody detection. The aim of this study was to assess the prevalence of inhibitors as measured by FLI. Assays of FVIII, FVIII inhibitor by Bethesda assay with Nijmegen modification, and FVIII inhibitor by FLI were performed on adult patients with haemophilia A. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 12 publications
0
25
0
2
Order By: Relevance
“…40 In contrast to our study which only included patients with severe hemophilia A (FVIII activity Ͻ 1%), the studies presented by Krudysz-Amblo et al, Lebreton et al, and Zakarija et al included patients with all severities of hemophilia A. 12,13,39 We believe that discrepancies in results for the prevalence of FVIII-binding antibodies between the various studies might be because of differences in the patient populations investigated and different assay formats. The study by Lebreton et al presented findings indicating that FVIII-binding antibodies found in patients without inhibitors are directed against light chain, heavy chain, or B-domain, with a clear dominance of antibodies directed against the heavy chain.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…40 In contrast to our study which only included patients with severe hemophilia A (FVIII activity Ͻ 1%), the studies presented by Krudysz-Amblo et al, Lebreton et al, and Zakarija et al included patients with all severities of hemophilia A. 12,13,39 We believe that discrepancies in results for the prevalence of FVIII-binding antibodies between the various studies might be because of differences in the patient populations investigated and different assay formats. The study by Lebreton et al presented findings indicating that FVIII-binding antibodies found in patients without inhibitors are directed against light chain, heavy chain, or B-domain, with a clear dominance of antibodies directed against the heavy chain.…”
Section: Discussionmentioning
confidence: 64%
“…For comparison, 3 recent studies using bead-based assays reported a prevalence of 50% (23 of 46), 33% (13 of 39), and 18% (28 of 210) for FVIII-binding antibodies in hemophilia A patients without inhibitors. 12,13,39 Another study which used an ELISA-based approach found a prevalence of 12% (6 of 49). 40 In contrast to our study which only included patients with severe hemophilia A (FVIII activity Ͻ 1%), the studies presented by Krudysz-Amblo et al, Lebreton et al, and Zakarija et al included patients with all severities of hemophilia A.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22]24,25,29,30 Several factors, particularly that all previous studies predominantly included patients with multiple transfusions, explain this large variation and the gaps in knowledge about their potential clinical role. For instance, the intron 22 inversion of FVIII mutation was associated with an increased frequency of NNAs in patients who had had multiple transfusions in 1 study 29 that was not confirmed in another study.…”
Section: Discussionmentioning
confidence: 99%
“…Their prevalence is approximately 2% to 3% in healthy individuals, 16,18,21,24 but estimates in patients who have hemophilia with different degrees of severity vary widely from 12% to 54%. [13][14][15][16][17][18][19][20][21][22]24,25,[29][30][31] Although NNAs and inhibitors cannot be distinguished on the basis of their isotypes, clonality, and epitopes, 32 recent data published by Hofbauer et al 16 indicate that anti-FVIII immunoglobulin G (IgG) with inhibitory activity has an up to 100-fold higher affinity for FVIII than IgG without inhibitory activity. On the basis of cross-reactivity studies, it has also been suggested that FVIII inhibitors in hemophilia A patients originate from the expansion of a natural anti-FVIII clone of B lymphocytes that exists before any treatment with FVIII and secretes anti-FVIII antibodies similar to the natural antibodies found in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The ELISA provides rapid screening that could be available well in advance of inhibitor confirmation by the Bethesda assay (77,78). Recently developed a new fluorescence-based immunoassay (FLI) was found to be much more sensitive for detecting especially low titre inhibitors (79).…”
Section: Diagnosis Of Inhibitorsmentioning
confidence: 99%